The association between midwifery staffing and reported harmful incidents: a cross-sectional analysis of routinely collected data - Lesley Turner; Jane Ball; Paul Meredith; Ellen Kitson-Reynolds; Peter Griffiths (BMC, 2024)
Abstract Background Independent inquiries have identified that appropriate staffing in maternity units is key to enabling quality care and minimising harm, but optimal staffing levels can be difficult to achieve when there is a shortage of midwives. The services provided and how they are staffed (total staffing, skill-mix and deployment) have been changing, and the effects of workforce changes on care quality and outcomes have not been assessed. This study aims to explore the association between daily midwifery staffing levels and the rate of reported harmful incidents affecting mothers and babies. Methods We conducted a cross-sectional analysis of daily reports of clinical incidents in maternity inpatient areas matched with inpatient staffing levels for three maternity services in England, using data from April 2015 to February 2020. Incidents resulting in harm to mothers or babies was the primary outcome measure. Staffing levels were calculated from daily staffing rosters, quantified in Hours Per Patient Day (HPPD) for midwives and maternity assistants. Understaffing was defined as staffing below the mean for the service. A negative binomial hierarchical model was used to assess the relationship between exposure to low staffing and reported incidents involving harm. Results The sample covered 106,904 maternal admissions over 46 months. The rate of harmful incidents in each of the three services ranged from 2.1 to 3.0 per 100 admissions across the study period. Understaffing by registered midwives was associated with an 11% increase in harmful incidents (adjusted IRR 1.110, 95% CI 1.002,1.229). Understaffing by maternity assistants was not associated with an increase in harmful incidents (adjusted IRR 0.919, 95% 0.813,1.039). Analysis of specific types of incidents showed no statistically significant associations, but most of the point estimates were in the direction of increased incidents when services were understaffed. Conclusion When there is understaffing by registered midwives, more harmful incidents are reported but understaffing by maternity assistants is not associated with higher risk of harms. Adequate registered midwife staffing levels are crucial for maintaining safety. Changes in the profile of maternity service workforces need to be carefully scrutinised to prevent mothers and babies being put at risk of avoidable harm.